Phosphoproteomic analysis of Methanohalophilus portucalensis FDF1(T) identified the role of protein phosphorylation in methanogenesis and osmoregulation - Wu, Wan-Ling (Sci Rep, 2016)
Methanogens have gained much attention for their metabolic product, methane, which could be an energy substitute but also contributes to the greenhouse effect. One factor that controls methane emission, reversible protein phosphorylation, is a crucial signaling switch, and phosphoproteomics has become a powerful tool for large-scale surveying. Here, we conducted the first phosphorylation-mediated regulation study in halophilic Methanohalophilus portucalensis FDF1(T), a model strain for studying stress response mechanisms in osmoadaptation. A shotgun approach and MS-based analysis identified 149 unique phosphoproteins. Among them, 26% participated in methanogenesis and osmolytes biosynthesis pathways. Of note, we uncovered that protein phosphorylation might be a crucial factor to modulate the pyrrolysine (Pyl) incorporation and Pyl-mediated methylotrophic methanogenesis. Furthermore, heterologous expression of glycine sarcosine N-methyltransferase (GSMT) mutant derivatives in the osmosensitive Escherichia coli MKH13 revealed that the nonphosphorylated T68A mutant resulted in increased salt tolerance. In contrast, mimic phosphorylated mutant T68D proved defective in both enzymatic activity and salinity tolerance for growth. Our study provides new insights into phosphorylation modification as a crucial role of both methanogenesis and osmoadaptation in methanoarchaea, promoting biogas production or reducing future methane emission in response to global warming and climate change.